COMMUNITY PERCEPTION OF PADANG VILLAGE, MANGGENG SUB-DISTRICT, SOUTHWEST ACEH DISTRICT ON THE IMPLEMENTATION OF SUSTAINABLE FOOD HOME AREA (KRPL) - Feni Riana; Devi Agustia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The purpose of this study was to describe the perceptions of the Padang Village Community, Manggeng District, Aceh Barat Daya District towards the Sustainable Food Home Area (KRPL). This research was conducted in Padang Village, Manggeng District, Southwest Aceh District. This research was conducted in January 2023 until completion. The sampling model in this study used simple random sampling, namely sampling regardless of strata in one population. the study population was 310 heads of households, the sampling approach from the population used the Slovin formula with a leeway of 15% (e = 15%). Then a sample of 39 heads of households can be drawn. The data sources to be used in this study consist of primary data and secondary data. The data analysis method in this study used a Likert Scale by looking at the comparison index of the total score of certain criteria, the perception index in this study was calculated. From the results of research on people's perceptionstowards the implementation of Sustainable Food Home Areas (KRPL) where each indicator can be categorized as very suitable for each indicator which inBenefit indicator with a grade point index of 87.30%, Ease of implementation indicator with a grade point index of 89.74%, Conformity indicator in application with a grade point index of 91.03% and KRPL Sustainability Indicators with a grade point index of 91.03%.